(3hUjI GdHfGJs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s ((3eMeO Hf CSYO Hf RjO Hf CMeO GdePMLi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HOhGe MeOg ESJMb ef GdYHO MeOg , hHENdGU YHGOJg CUGH GdeJYHO QTOg CeG HYO aEf Mb GdhGdO Ydi GdhdO jJQJH Ydi bjGe GdhGdO HMb GdhdO s
(3BNQgG (B:s
(3hCfG CSJZaQ Gddg hCJhH Edjg hCSCdg GdYah hGdYGajI ai GdOfjG hGdBNQI hGdSdGe Ydjge CLeYjf JeJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs